Genotoxicidad del agua contaminada por plaguicidas en un área de Antioquia (2011)
ABSTRACT: Determining genotoxicity of organic extract from water resources contaminated by the pesticides used in agriculture, pig and poultry production in Monterredondo village (Antioquia), as a diagnosis of its quality to understand its influence on these water sources in San Pedro de Los Milagros (Antioquia). Materials and methods. Comet assay was used to establish osmotic fragility of erythrocytes, cell viability and DNA damage in human lymphocytes by incubating of these cells in three samples of water collected from sources in the village of Monterredondo in the laboratory of Biochemistry, Faculty of Medicine of the University Antioquia. Results. Data analysis of the comet’s assay length of the organic extract from the three collected samples, indicates genotoxicity. This effect is dependent on the concentration of the extract and the sampling site (p<0.001). The sample of water from the Hato River shows the highest genotoxic effect at 4 and 37ºC. The water sample, from treatment plant Hacienda La Montaña shows relative high genotoxicity, compared to the sample water taken from Fray Juana river. Conclusions. The analysis of the three water samples, collected in the Monterredondo village, reveals genotoxicity. However, further evaluation on the toxicity grade of the concentrated organic components and the genotoxicity in people who drink it, is suggested.